Register-based and genetic studies of Prader-Willi syndrome show a high frequency of gonadal tumors and a possible mechanism for tumorigenesis through imprinting relaxation - Maya-González, Carolina; Wessman, Sandra; Lagerstedt-Robinson, Kristina; Taylan, Fulya; Tesi, Bianca; Kuchinskaya, Ekaterina; McCluggage, W. Glenn; Poluha, Anna; Holm, Stefan; Nergårdh, Ricard; Díaz De Ståhl, Teresita; Höybye, Charlotte; et al. (Frontiers in Medicine, 2023)
Prader-Willi Syndrome (PWS) is a rare disease, caused by lack of expression of inherited imprinted genes in the paternally derived Prader-Willi critical region on chromosome 15q11.2-q13. PWS is characterized by poor feeding and hypotonia in infancy, and intellectual disability, behavioral abnormalities, dysmorphic features, short stature, obesity, and hypogonadism. PWS is not a known cancer predisposition syndrome, but previous investigations regarding the prevalence of cancer in these patients suggest an increased risk of developing specific cancer types such as myeloid leukemia and testicular cancer. We present results from a Swedish national population-based cohort study of 360 individuals with PWS and 18000 matched comparisons. The overall frequency of cancer was not increased in our PWS cohort, but we found a high frequency of pediatric cancers, especially gonadal tumors. We also performed whole-genome sequencing from blood-and tumor-derived DNA from a unilateral dysgerminoma in a 13-year-old girl with PWS who also developed bilateral ovarian sex cord tumors with annular tubules (SCTATs). In germline analysis there were no additional findings apart from the 15q11.2-q13 deletion of the paternal allele, while a pathogenic activating KIT mutation was identified in the tumor. Additionally, methylation-specific multiplex ligation-dependent probe amplification revealed reduced methylation at the PWS locus in the dysgerminoma but not in blood. In conclusion, our register-based study suggests an increased risk of cancer at young age, especially testicular and ovarian tumors. We found no evidence of a general increase in cancer risk in patients with PWS. However, given our limited observational time, further studies with longer follow-up are needed to clarify the life-time cancer risk in PWS. We also describe the second case of locus-specific loss-of-imprinting in a germ-cell tumor in PWS, suggesting a possible mechanism of carcinogenesis.